2021
DOI: 10.1002/jnr.24779
|View full text |Cite
|
Sign up to set email alerts
|

Extra‐striatal dopamine in Parkinson's disease with rapid eye movement sleep behavior disorder

Abstract: Rapid eye movement sleep behavior disorder (RBD) is a common condition found in more than 50% of the patients with Parkinson's disease (PD). Molecular imaging shows that PD with RBD (PD-RBD+) have lower striatal dopamine transporter activity within the caudate and putamen relative to PD without RBD (PD-RBD−).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 64 publications
(110 reference statements)
3
10
0
Order By: Relevance
“…As there were main effects of MoCA [F (2, 42) = 7.29, p = 0.002] and BDI [F (2, 42) = 3.89, p = 0.028], we followed up with Bonferroni post hoc t-tests to detect where the group differences occurred. These particular results were reported previously by Valli et al (23). In summary for BDI, patients with RBD had the highest depression score, then PD patients without RBD, then healthy controls.…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…As there were main effects of MoCA [F (2, 42) = 7.29, p = 0.002] and BDI [F (2, 42) = 3.89, p = 0.028], we followed up with Bonferroni post hoc t-tests to detect where the group differences occurred. These particular results were reported previously by Valli et al (23). In summary for BDI, patients with RBD had the highest depression score, then PD patients without RBD, then healthy controls.…”
Section: Resultssupporting
confidence: 89%
“…Previous literature shows other molecular structures and neurotransmitters may play a larger role contributing to RBD in PD apart from DAT (14,16,44). Outside the striatum, our group showed a negative relationship where D2 receptor availability within the uncus parahippocampus decreased with increasing disease severity in PD patients with RBD relative to PD patients without RBD (23). Other studies showed altered cholinergic (45) and noradrenaline levels (49), along with changes in glucose metabolic activity (15) in PD patients with RBD relative to patients without RBD, suggesting RBD pathophysiology in PD is multi-systemic that impacts regions beyond the striatum.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…A total of 45 participants were enrolled in this study: 15 PD patients without probable RBD, 15 PD patients with probable RBD, and 15 age-matched healthy controls (Table 1 ). Some of the imaging, demographic, cognitive and psychological data from these participants have been reported previously [ 23 , 24 ]. Both PD patient groups were diagnosed based on the UK Parkinson Disease Society Brain Bank criteria.…”
Section: Methodsmentioning
confidence: 99%